Board diversity, IPO underpricing, and firm value: Evidence from Korea - Kyung Hee Park; Jinho Byun (Global Business & Finance Review (GBFR), 2022)
Purpose: We investigate the impact of board diversity on initial public offering underpricing and firm value. Design/methodology/approach: We examine the relationship between board diversity and IPO underpricing by collecting data on the board size and composition of 470 IPOs listed on the Korea Exchange (KRX) for the period 1999-2018. Findings: We find a significant average first-day return (35.24%), similar to the results of previous studies on IPO underpricing, but the underpricing decreases with an increase in board diversity. Using first-day returns and Tobin's Q as measures of underpricing and firm value, respectively, we find that a larger and more diverse board of directors maximizes shareholder wealth. Specifically, when measured by Tobin's Q, firm value is positively related to the percentage of outside directors and board size. Gender diversity on the board, growth opportunities, and profitability positively influence firm value. Employing a dummy variable for female members to measure the presence of female directors on a board, we find that the presence of female directors significantly enhances firm value. Research limitations/implications: This study has implications for theories of corporate governance in the body of literature on financial decision-making. It analyzes how diversity in boards of directors plays a critical role in determining IPO prices, together with how diversity affects the future value of firms. However, this study still has some limitations in that the effects of IPO underpricing and corporate governance have not been completely analyzed. Therefore, we expect that further studies on additional variables will be conducted to provide meaningful implications. Originality/value: This study bridges the gap between corporate governance and IPO underpricing literature. While many theories on IPO underpricing have been rigorously examined, few have investigated the effects of the board of directors. We analyze how diversity in boards of directors plays a critical role in determining IPO prices, together with how diversity affects the value of firms.
Keywords: 650; Board of directors; Board diversity; Corporate governance; Initial public offering; Underpricing